The impact of export shocks on child health: evidence from China - Yu-Ting Zhang; Yu-Ting Zhang; Oksana Vladimirovna Mashevskaya; Xiu-Zhi Wang (Frontiers in Public Health)
BackgroundAmidst sluggish global economic growth and rising anti-globalization sentiments, it has become imperative to reassess the benefits and hidden costs of globalization. Simultaneously, with the fading of the “demographic dividend” and the intensification of population aging, understanding children’s health and its underlying determinants is crucial for sustainable socio-economic development. China provides an ideal case for examining these issues.MethodsUsing data from the China Health and Nutrition Survey (CHNS) and UN Comtrade Database, this study constructs a four-period unbalanced panel and empirically investigates the impact of export expansion on children’s health in China during the country’s trade liberalization process. To address potential endogeneity concerns, we employ a Bartik-IV model to construct an export shock variable and identify the effect of trade exposure on child morbidity.ResultsRegression estimates reveal that export shocks are significantly associated with improved child health. Specifically, a one-standard-deviation increase in export exposure reduces the probability of child morbidity by 14 percentage points. Mediation analysis identifies four key channels: parental fixed income, employment rates, work intensity, and left-behind child status. Export-induced increases in parental wages and paternal employment are linked to better child health, while paternal work intensity also shows a protective effect. In contrast, increased maternal work intensity may worsen child outcomes. Export shocks also raise the incidence of left-behind children, with differing effects by gender. Heterogeneity analysis reveals that health gains from trade are concentrated among boys, urban children, and those in western China.ConclusionTrade liberalization can yield important health benefits for children, but these gains are not evenly distributed. Policies should aim to strengthen positive mechanisms such as stable parental employment and income, while also addressing potential risks associated with increased maternal labor demands and child separation. Particular attention should be paid to left-behind girls and to children living in rural areas of central and eastern China. Expanding investment in public health infrastructure, strengthening social protection systems, and ensuring equitable access to education are essential for making trade-driven growth conducive to inclusive and sustainable improvements in child health.